Professional Security Management and Investigation for the New Competitive Advantage - Button, Mark; Lee, Ju-Lak; Kim, Hak-Kyong (International JOURNAL OF CONTENTS, 2011)
This paper is mainly associated with setting out an agenda for the transformation of security by creating a new framework for a security system, which can maximise its effectiveness. Noticeably, this research shows empirically that crimes are getting a major cost to organisations, which if reduced by security and investigations could reap substantial rewards to the finances of an organisation. However, the problem is that the delivery of security is frequently delegated to personnel (e.g. security guards) with limited training, inadequate education, and no real commitment to professionalism –‘sub-prime’ security, finally causing security failures. Therefore, if security can be enhanced to reduce the crime cost, this will produce financial benefits to business, and consequently could produce a competitive advantage. For this, the paper basically draws upon Luke’s theoretical framework for deconstructing ‘power’ into three dimensions. Using this three-dimensional approach, the paper further sets out a model of how security can be enhanced, utilising a new Security Risk Management (SRM) model, and how can this SRM model create competitive advantage in business. Finally, this paper ends with the six strategies needed to enhance the quality of security: refiguring as SRM, Professional Staff, Accurate Measurement, Prevention, Cultural Change, and Metrics. This paper is mainly associated with setting out an agenda for the transformation of security by creating a new framework for a security system, which can maximise its effectiveness. Noticeably, this research shows empirically that crimes are getting a major cost to organisations, which if reduced by security and investigations could reap substantial rewards to the finances of an organisation. However, the problem is that the delivery of security is frequently delegated to personnel (e.g. security guards) with limited training, inadequate education, and no real commitment to professionalism –‘sub-prime’ security, finally causing security failures. Therefore, if security can be enhanced to reduce the crime cost, this will produce financial benefits to business, and consequently could produce a competitive advantage. For this, the paper basically draws upon Luke’s theoretical framework for deconstructing ‘power’ into three dimensions. Using this three-dimensional approach, the paper further sets out a model of how security can be enhanced, utilising a new Security Risk Management (SRM) model, and how can this SRM model create competitive advantage in business. Finally, this paper ends with the six strategies needed to enhance the quality of security: refiguring as SRM, Professional Staff, Accurate Measurement, Prevention, Cultural Change, and Metrics. KCI Citation Count: 1